Protein Tyrosine Nitration in Plant Nitric Oxide Signaling - León, José (Frontiers in Plant Science, 2022)
Nitric oxide (NO), which is ubiquitously present in living organisms, regulates many developmental and stress-activated processes in plants. Regulatory effects exerted by NO lies mostly in its chemical reactivity as a free radical. Proteins are main targets of NO action as several amino acids can undergo NO-related post-translational modifications (PTMs) that include mainly S-nitrosation of cysteine, and nitration of tyrosine and tryptophan. This review is focused on the role of protein tyrosine nitration on NO signaling, making emphasis on the production of NO and peroxynitrite, which is the main physiological nitrating agent; the main metabolic and signaling pathways targeted by protein nitration; and the past, present, and future of methodological and strategic approaches to study this PTM. Available information on identification of nitrated plant proteins, the corresponding nitration sites, and the functional effects on the modified proteins will be summarized. However, due to the low proportion of in vivo nitrated peptides and their inherent instability, the identification of nitration sites by proteomic analyses is a difficult task. Artificial nitration procedures are likely not the best strategy for nitration site identification due to the lack of specificity. An alternative to get artificial site-specific nitration comes from the application of genetic code expansion technologies based on the use of orthogonal aminoacyl-tRNA synthetase/tRNA pairs engineered for specific noncanonical amino acids. This strategy permits the programmable site-specific installation of genetically encoded 3-nitrotyrosine sites in proteins expressed in E. coli, thus allowing the study of the effects of specific site nitration on protein structure and function.